Structural and biochemical studies of Sporosarcina pasteurii UreE: a nickel-chaperone involved in the urease activation process - Merloni, Anna <1984> (Alma Mater Studiorum - Università di Bologna, 2014)
Urease is a nickel-dependent enzyme that catalyzes hydrolysis of urea in the last step of organic nitrogen mineralization. Its active site contains a dinuclear center for Ni(II) ions that must be inserted into the apo-enzyme through the action of four accessory proteins (UreD, UreE, UreF, UreG) leading to activation of urease. UreE, acting as a metallo-chaperone, delivers Ni(II) to the preformed complex of apo-urease-UreDFG and has the capability to enhance the GTPase activity of UreG. This study, focused on characterization of UreE from Sporosarcina pasteurii (SpUreE), represents a piece of information on the structure/mobility-function relationships that control nickel binding by SpUreE and its interaction with SpUreG. A calorimetric analysis revealed the occurrence of a binding event between these proteins with positive cooperativity and a stoichiometry consistent with the formation of the (UreE)2-(UreG)2 hetero-oligomer complex. Chemical Shift Perturbations induced by the protein-protein interaction were analyzed using high-resolution NMR spectroscopy, which allowed to characterize the molecular details of the protein surface of SpUreE involved in the complex formation with SpUreG. Moreover, backbone dynamic properties of SpUreE, determined using 15N relaxation analysis, revealed a general mobility in the nanoseconds time-scale, with the fastest motions observed at the C-termini. The latter analysis made it possible for the first time to characterize of the C-terminal portions, known to contain key residues for metal ion binding, that were not observed in the crystal structure of UreE because of disorder. The residues belonging to this portion of SpUreE feature large CSPs upon addition of SpUreG, showing that their chemical environment is directly affected by protein-protein interaction. Metal ion selectivity and affinity of SpUreE for cognate Ni(II) and non cognate Zn(II) metal ions were determined, and the ability of the protein to select Ni(II) over Zn(II), in consistency with the proposed role in Ni(II) cations transport, was established.